Airport pavement roughness evaluation through aircraft dynamic response - Cossío Durán, Jorge Braulio (2019)
Airport pavements and longitudinal elevation profiles, in conjunction with the aircraft, form a system where vertical displacements are produced that can compromise their performance. Rough pavements are generally responsible for the occurrence of dynamic responses such as vertical accelerations and pavement loads that affect the aircraft, increase stopping distance and difficult to read the cockpit instrumentation. To approach this problem, the International Roughness Index (IRI) and the Boeing Bump Index (BBI) are currently used to quantify airport pavement roughness and to identify sections that need maintenance and rehabilitation (M&R) activities. However, such indices were developed only based on the dynamic responses of an automobile at 80 km/h to the irregularities of road pavements, and from the physical characteristics of the irregularities, respectively, without considering the effect of the aircraft dynamic response. In addition, current critical limits for IRI and BBI can misjudge the real condition of the pavement. This research aims to evaluate the effect of airport pavement roughness on aircraft dynamic response in terms of vertical accelerations at the aircraft cockpit (VACP) and at the center of gravity (VACG), as well of dynamic loads at the nose, main and rear landing gear (NGPL, MGPL, and RGPL), which may compromise the aircraft safety and the pavement performance. The ProFAA software was used to compute both indices and to simulate the responses of 4 representative aircraft traversing 20 runway profiles at 10 operational speeds varying from 20 to 200 knots (37 to 370 km/h). Statistical comparisons and regression analyses between roughness indices and dynamic responses were carried out. Principal results indicated that VACP was 50% higher than VACG and that NGPL was approximately 80% higher than MGPL. In addition, it was observed that VACP exceeds 0.40 g when the IRI is higher than 3.7 m/km and that NGPL doubles the static load when the IRI is higher than 3.3 m/km. A case study presented to compare these limits shown that decision-making based on the dynamic response of the aircraft can bring significant differences in the number and quality of M&R activities.